Implementation of Electronic Module Based Multiple Representation on Buffer Solution Materials to Improve Students’ Self-Regulated Learning and Cognitive Learning Outcomes - Irfan Kamaludin Syam; Isana Supiah Yosephine Louise (Jurnal Penelitian Pendidikan IPA, 2023)
This research aims to determine the differences between self-regulated learning (SRL) and cognitive learning outcomes (CLO) of students who use multiple representation-based e-modules with students who use other teaching materials without being based on multiple representations on buffer solution materials and to determine the percentage of effective contribution. The subjects of this study were students of class XI MIPA at one of the high schools in Yogyakarta. The sampling technique carried out is cluster random sampling with a quasi-experiment method by posttest-only control group design. The instruments used are questionnaires on self-regulated learning and cognitive learning outcomes. The data analysis technique used in the field test results used Hotelling's Trace test and the results of effective contribution were obtained from the Partial Eta Squared value. The results showed that the significance value of 0.000 < 0.05 so that H0 was rejected, which means that there are differences in SRL and CLO of students between students who use multiple representation-based e-modules and students who use other teaching materials without multiple representations based on buffer solution materials. The percentage of effective contribution of the use of e-modules to SRL by 16.5%, CLO by 11.8%, and SRL and CLO by 20.3%.